Desain Istruksional dan Pendekatan Transdisipliner dalam Pembelajaran Pendidikan Agama Islam - Halik; Hadi Machmud; Nurdin; Imelda Wahyuni; Rahmat (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine and construct an instructional design based on a transdisciplinary approach as a response to the complexity of educational problems in the global era. The transdisciplinary approach emphasizes cross-disciplinary integration to produce holistic and solution-oriented understanding of reality. The method used is a literature study with a conceptual-critical approach. The findings show that conventional instructional design, which is linear and disciplinarily fragmented, has limitations in accommodating the internalization of Islamic values that are reflective and contextual. The transdisciplinary approach offers an integrative framework that positions real-world problems as the starting point of learning and encourages epistemic dialogue between revelation, reason, and social reality. The conceptual model formulated includes analysis of real contexts, identification of transdisciplinary issues, integration of Islamic values, design of problem-based activities, and reflective evaluation. The implementation of this approach faces challenges such as educator readiness, curriculum limitations, and resistance to paradigm change. The contribution of this research is the formulation of an instructional design framework that is integrative, contextual, and adaptive to the development of science and technology, while maintaining the integrity of Islamic values as an ethical and spiritual foundation